2001
DOI: 10.1002/ep.670200212
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of biodegradation kinetic parameters for naphthalene in batch and sand column systems by pseudomonas putida

Abstract: Kinetic parameters for the degradation of naphthalene by Pseudomonas putida ( ATCC 17484) were estimated in both batch and column assays, in order to evaluate the role of flow and cell attachment on biodegradation rates. Suspended cells and cells attached to Ottawa sand were used under a variety of biomass levels, column flow‐rates, and substrate concentrations. In batch systems, degradation followed zero order kinetics across the entire concentration range, while the columns exhibited decreased rates at conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
(31 reference statements)
1
9
0
Order By: Relevance
“…A similar effect is not observed at Rattekaai, however. Flow-through experiments with intact sediments from Appels and Waarde may experience a higher degree of what Park et al (2001) refer to as reactive heterogeneity: all flow paths do not necessarily sample the same biomass and therefore do not experience the same reaction history. The lack of mass transfer limitation in Rattekaai sediment may be due to the much higher SRB densities and higher sediment porosities, as these would reduce the transfer distances of dissolved substrates from the pore water medium to particle-bound SRB cells.…”
Section: Transport Limitation Of Sulfate Reductionmentioning
confidence: 97%
See 1 more Smart Citation
“…A similar effect is not observed at Rattekaai, however. Flow-through experiments with intact sediments from Appels and Waarde may experience a higher degree of what Park et al (2001) refer to as reactive heterogeneity: all flow paths do not necessarily sample the same biomass and therefore do not experience the same reaction history. The lack of mass transfer limitation in Rattekaai sediment may be due to the much higher SRB densities and higher sediment porosities, as these would reduce the transfer distances of dissolved substrates from the pore water medium to particle-bound SRB cells.…”
Section: Transport Limitation Of Sulfate Reductionmentioning
confidence: 97%
“…6B highlight the ambiguities associated with comparing kinetic parameters obtained using different experimental approaches (Park et al, 2001). In sediment slurry experiments, microbial aggregates as well as particle-bound biofilms are disrupted (Marxsen and Fiebig, 1993), which results in an increase of free-living cells over particle-bound cells.…”
Section: Half-saturation Concentrations For Sulfatementioning
confidence: 99%
“…The batch growth kinetics on naphthalene and 2-methylnaphthalene were simulated using fi rst order growth kinetics assuming that PAHs were the limiting substrates. First order kinetics is a reasonable assumption for the growth of P. putida on naphthalene since it has been shown that the saturation constant is considerably less than 1 mg/l (Park et al, 2001;Alshafi e and Ghoshal, 2003). However, the removal rates of the substrates (and therefore the growth rate of the bacteria) were limited by the maximum mass transfer rates of the substrates from the solid particles to the aqueous media, which differed for each type of bioreactor and each substrate.…”
Section: Resultsmentioning
confidence: 99%
“…Anekpankul and Goto [31] suggested that extraction is controlled by intraparticle diffusion which is related to water flow rate. Therefore, it is expected that a high flow rate reduces external mass transfer resistance and increases extraction efficiency [32]. In this study, several flow rate conditions, 0.5, 1.0, 1.5, and 2.0 mL/min, were examined at the constant temperature of 250 8C and extraction time of 30 min ( Table 4).…”
Section: Influence Of Water Flow Rate On Removal Efficienciesmentioning
confidence: 99%